PARAMETERS OF MODEL VARIETIES OF SPRING BARLEY - E. G. Filippov (Зерновое хозяйство России, 2018)
The success of breeding is largely defined by a proper choice of the best agro eco type.  A long-term study (1981-2014) of the various collection and breeding material of the zoned varieties, a retrospective analysis of barley researches on Don, a study of correlations among productivity and its elements, i.e. resistance to stress, lodging and diseases, gave an opportunity to ascertain a number of traits which should become characteristic for new developed varieties; to develop schemes of the best parameters of model varieties of different idiotypes and trends of their economic use in the Rostov region.  The recommended models of spring barley of various economic uses allow receiving a maximum yield per each hectare, sown with new varieties. In the Rostov region there are some differences among soil-climatic areas due to their soil fertility, temperature regime, amount and time of precipitations.  In the north-western, north-eastern and eastern parts the varieties of half-intensive type give higher yields, as a trait of ecologic stability plays the main part here. In the Central irrigated area, in southern and pre-Azov areas preference should be given to the varieties of intensive idiotypes, which are characterized with early maturity, good realization of accumulated assimilators and ability to produce a complete yield in the first decade of July because of the ability to avoid summer droughts in the period of grain ripening.